2015
DOI: 10.15241/rgc.5.3.365
|View full text |Cite
|
Sign up to set email alerts
|

Examining Intimate Partner Violence, Stress and Technology Use Among Young Adults

Abstract: Intimate partner violence is a problem among young adults and may be exacerbated through the use of technology. Scant research exists examining the influence of technology on intimate partner violence in young adults. Furthermore, young adult couples on university campuses experience additional stressors associated with coursework that may influence their risk of partner violence. We surveyed 138 young adults (ages 18-25) at a large university and examined the relationships between stress, intimate partner vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In line with previous research, Carlson, Fripp, Cook, and Kelchner () found that an imbalance in technology use between intimate partners is a risk factor for IPV. A more recent study found that adolescents in romantic relationships felt pressured to keep in contact with their partner via communication technologies (Agnew‐Brune, ).…”
Section: Technology‐facilitated Abuse/violence In Teen/young People'ssupporting
confidence: 87%
“…In line with previous research, Carlson, Fripp, Cook, and Kelchner () found that an imbalance in technology use between intimate partners is a risk factor for IPV. A more recent study found that adolescents in romantic relationships felt pressured to keep in contact with their partner via communication technologies (Agnew‐Brune, ).…”
Section: Technology‐facilitated Abuse/violence In Teen/young People'ssupporting
confidence: 87%
“…A lack of significant relationship between CDA victimization and other well-being domains, such as stress and relationship satisfaction, is consistent with previous research. There is prior evidence that no association exists between stress and CDA victimization (Carlson et al, 2015). Although no specific studies have investigated associations between CDA victimization and relationship satisfaction, even evidence of an association between in-person IPV victimization and relationship satisfaction is mixed (e.g., Amanor-Boadu et al, 2011; Kaura & Lohman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that, even when controlling for other victimization experiences, alcohol use continues to be related to CDA victimization among emerging adults (Bennett, Guran, Ramos, & Margolin, 2011). Other studies have reported a lack of relationship between CDA victimization and general stress without controlling for in-person IPV victimization among emerging adults (Carlson, Fripp, Cook, & Kelchner, 2015). Thus, it appears that CDA may have some associations with psychosocial functioning, but it remains unclear exactly to what extent CDA victimization may have a unique association beyond other forms of victimization.…”
Section: Cda Victimization and Psychosocial Functioningmentioning
confidence: 95%
“…However, the relationship between IPVAW, technologies, and young people seems more complex. A study conducted by Carlson et al (2015) among undergraduate and graduate students aged 18 to 25 years found that those who perceived their partner to use technology more (i.e., monitor, embarrass, make them feel bad, control, argue) were also the ones at less risk to suffer violence. This supports the idea that younger generations may use technology to communicate differently when compared with the older population, and that it may be a requirement for young adult relationships to do so in order not to increase tension in the couple (Carlson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a further possible explanation for the high prevalence of IPVAW among younger people is that they belong to a generation—mostly millennials and Generation Z—whose use of technology, as compared to other generations, may facilitate or create new ways of experiencing and perpetrating IPVAW (Carlson et al, 2015; Dimond et al, 2011; Duerksen & Woodin, 2019; Marganski & Melander, 2018; Stonard, 2021; Woodlock, 2017). IPVAW has been related to digital technologies, not only because they provide a wider range of ways in which the perpetrator can exert control over the victim, but also because they make it difficult to set boundaries within an intimate relationship in terms of digital privacy or to erase the abuser from one’s life when social circles online are shared (Carlson et al, 2015; Dimond et al, 2011; Duerksen & Woody, 2019; Freed et al, 2017; Marganski & Melander, 2018; Stonard, 2021; Woodlock, 2017). However, the relationship between IPVAW, technologies, and young people seems more complex.…”
Section: Discussionmentioning
confidence: 99%